STRATEGI MENGOPTIMALKAN PERANAN PENDAPATAN ASLI DESA (PADES) DALAM MENGHADAPI TANTANGAN FAKTOR RENDAHNYA KONSTRIBUSI PADES DI LEMBAGA PTX - Lestari, Ayu Dwi; Jannah, Binti Shofiatul (Cahaya Ilmu Bangsa, 2024)
This research aims to analyze optimal strategies in increasing the role of Village Original Income (PaDes) in Lamongan Regency in order to face the challenge of low PaDes contribution to village development. Using descriptive qualitative methods, data was collected through in-depth interviews and document analysis to identify causal factors and relevant solutions. The research results show that the low contribution of PaDes is caused by limited human resource capacity, lack of exploration of local potential, and minimal application of technology. The proposed strategy includes training village officials, diversifying PaDes sources, and utilizing digital technology for transparency and accountability.